2017
DOI: 10.3389/fmicb.2017.02566
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antibiotic Susceptibility and Diversity of Vibrio parahaemolyticus Isolates in Seafood from South China

Abstract: Vibrio parahaemolyticus is a leading cause of foodborne infections in China and a threat to human health worldwide. The main objective of this study is to determine the prevalence and characteristic of V. parahaemolyticus isolates in fish, oyster and shrimp samples from the South China domestic consumer market. To accomplish this, we examined 504 seafood samples from 11 provinces of China. The prevalence rates were 9.38, 30.36, and 25.60%, respectively. In summer (33.33%), the prevalence of V. parahaemolyticus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 50 publications
(61 reference statements)
13
32
1
Order By: Relevance
“…In fact, 64% of the Vibrio isolates were resistance to at least three or more antibiotics. These findings were similar with a previous study reported that 68% of the Vibrio isolates were resistance to at least three or more antibiotics (Yang et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In fact, 64% of the Vibrio isolates were resistance to at least three or more antibiotics. These findings were similar with a previous study reported that 68% of the Vibrio isolates were resistance to at least three or more antibiotics (Yang et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Over 80% of V. harveyi from fish in Italy showed resistant to ampicillin, amoxicillin and erythromycin (Scarano et al, 2014). The findings were also in agreement with studies done all around world and Malaysia (Ang et al, 2010;Al-Othrubi et al, 2014;Elexson et al, 2014;Saifedden et al, 2016;Tan et al, 2017). Emergence of high resistance Vibrio strains against ampicillin and penicillin was related with the extensive used of both antibiotics and could influence the disease management in aquaculture system (FAO, 2017).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Table 1 shows examples of studies that have investigated the presence of V. parahaemolyticus in oysters collected from either culturing environments or markets in either tropical, subtropical, or temperate areas. Oyster samples collected from tropical or subtropical areas (Cook et al., 2002; Deepanjali et al., 2005; DePaola, Nordstrom, Bowers, Wells, & Cook, 2003; Han et al., 2017; Johnson et al., 2010, 2012; López‐Hernández, Pardío‐Sedas, Lizárraga‐Partida, Williams, Martínez‐Herrera, Flores‐Primo, Uscanga‐Serrano, & Rendón‐Castro, 2015; Matté, Matté, Rivera, & Martins, 1994; New et al., 2014; Sanjeev & Stephen, 1993; Sobrinho et al., 2010, 2011; Ward & Bej, 2006; Yang et al., 2017; Yu et al., 2013, 2016; Zimmerman et al., 2007) are generally considered to exhibit higher concentrations of V. parahaemolyticus than those obtained from temperate areas (Cruz et al., 2015; Duan & Su, 2005b; Fletcher, 1985; Jones et al., 2014; Kaysner, Abeyta, Stott, Krane, & Wekell, 1990; Kaysner, Abeyta, Stott, Lilja, & Wekell, 1990; Kirs et al., 2011; Lopatek, Wieczorek, & Osek, 2015; Lopez‐Joven et al., 2015; Mok et al., 2019; Nakaguchi, 2013; Park, Mok, et al., 2018; Parveen et al., 2008; Roque et al., 2009; Ryu, Mok, Lee, Kwon, & Park, 2019; Tepedino, 1982; Thomson & Thacker, 1972). For example, concentrations of V. parahaemolyticus in oysters were 94% in India, between 77% and 100% in Brazil, 100% in Mexico, and 71% in Taiwan.…”
Section: Distribution Of V Parahaemolyticus In Oystersmentioning
confidence: 99%